3D-printing a 'family' of biomimetic models to explain armored grasping in syngnathid fishes. (6th November 2017) - Porter, Michael M; Ravikumar, Nakul
Abstract: Seahorses and pipehorses evolved at least two independent strategies for tail grasping, despite being armored with a heavy body plating. To help explain mechanical trade-offs associated with the different designs, we created a 'family' of 3D-printed models that mimic variations in the presence and size of their armored plates. We measured the performance of the biomimetic proxies across several mechanical metrics, representative of their protective and prehensile capacities. Our results show that the models mimicking the tails of seahorses are the best all-around performers, while those of the distal-most, prehensile region of pipehorses are more flexible, but less protected. The comparison also reveals that different adaptive strategies provide different task-specific performance advantages, which could be leveraged for the design of armored manipulators or other bio-inspired technologies.